2013
DOI: 10.1021/jp403032e
|View full text |Cite
|
Sign up to set email alerts
|

How Much Water Is Needed To Ionize Formic Acid?

Abstract: Structure, molecular properties, energy parameters, and vibrational IR spectra of hydrated clusters of formic acid (FOH), FOH·nH2O (n = 1-8), are presented following first principle based electronic structure theory. Several geometrical arrangements are considered as initial guess structures to look for the minimum energy equilibrium structures applying ωB97X-D density functional and aug-cc-pVDZ set of atomic basis functions. Results on FOH-water clusters suggest that the most stable structure of formic acid e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…n H 2 O.H + ) took place for some value of n (= N G i ). Microhydrated cluster structures published by Maity and co-workers for structurally analogous formic [ 27 ] and trifluoroacetic acid [ 28 ] and by Leopold for various acids [ 21 ] served as useful models for the starting points for optimizations. The larger hydration clusters ( n > ~8) displayed potential energy surfaces with quite a lot of shallow local minima, such that extensive searching was needed to find the global minima.…”
Section: Resultsmentioning
confidence: 99%
“…n H 2 O.H + ) took place for some value of n (= N G i ). Microhydrated cluster structures published by Maity and co-workers for structurally analogous formic [ 27 ] and trifluoroacetic acid [ 28 ] and by Leopold for various acids [ 21 ] served as useful models for the starting points for optimizations. The larger hydration clusters ( n > ~8) displayed potential energy surfaces with quite a lot of shallow local minima, such that extensive searching was needed to find the global minima.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, the general interest is to probe the minimum number of solvent molecules required for acid dissociation and concurrent proton transfer process, to understand the acid dissociation phenomenon at a molecular level. [2][3][4][5][6] In this regard, the role of ammonia as a solvent in the proton transfer process in the phenol-(ammonia)n clusters have been the subject of intense experimental and theoretical investigations by several research groups over the past three decades to understand the proton transfer reaction in the ground state and hydrogen transfer process in the excited electronic state. [7][8][9][10][11][12][13][14][15][16] Additionally, it has been shown that the excited proton transfer reaction of phenol becomes ultrafast at the air-water interface.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, we present a calculation of the IR spectrum of the SIP in a fashion that isolates the contribution from the signature hydronium ion, H 3 Fundamental studies of acids in biological and chemical contexts are obviously of great and intense interest. [6][7][8][9][10][11][12] The answer is typically sought by detecting the presence or absence of signature spectral features of the hydrated proton in the infra-red. [6][7][8][9][10][11][12] The answer is typically sought by detecting the presence or absence of signature spectral features of the hydrated proton in the infra-red.…”
mentioning
confidence: 99%